Molecular modeling of inhibitors against fructose bisphosphate aldolase from Candida albicans - de Amorim, Andréia Lima (In Silico Pharmacol, 2018)
Candida albicans is an opportunistic pathogen that causes from vulvovaginal and oropharyngeal candidiasis to systemic infections. The enzyme 1,6-fructose bisphosphate aldolase class II (FBA II), is a macromolecule existing only in lower organisms, being essential for the survival of the pathogen due to its function of maintaining the glycolysis process. The aim of this paper was to evaluate the inhibitors of FBA II regarding their physicochemical, pharmacokinetic and toxicological properties and apply concepts of rational drug development to propose new compounds for the treatment of fungal infections of C. albicans. Physicochemical (HyperChem software and the webserver cactus) and ADME/Tox (PreADMET webserver) properties were calculated to four inhibitors described in the literature and three analogues. None of the compounds presented in this study violated RO5, however all inhibitors demonstrated low or moderate human intestinal absorption (HIA), as well as low or moderate permeability in Caco-2 and MDCK, poor plasma proteins binding (PPB) and low permeability of the blood–brain barrier (BBB); however, Compound 4 is the exception for BBB permeability, being also the only non-mutagenic compound, and therefore, used as a lead compound. Analogues B and C presented high HIA, weak PPB and low BBB permeability, as well as a positive prediction for carcinogenicity in rats and mouse and non-mutagenicity in the Ames test. Through the evaluations carried out, it was concluded that the analogues B and C have proved to be promising candidates for oral administration drugs in the treatment of fungal infections of the genus Candida.